Intraoperative AIRO mobile computer tomography in frameless stereotactic procedures. (4th July 2022) - Riva, Marco; Arcidiacono, Umberto A.; Gambaretti, Matteo; Gay, Lorenzo G.; Sciortino, Tommaso; Rossi, Marco; Conti Nibali, Marco; Bello, Lorenzo
Abstract: Background: Multiple factors can affect the accuracy of neuronavigation, that is a relevant issue, particularly for frameless stereotactic procedures, where precision and optimal image-guidance is crucial for the surgical performance, workflow, and outcome. Objective: To investigate the impact of AIRO Mobile Computer Tomography in frameless stereotactic approaches. Methods: A retrospective study on 12 patients was performed. All the procedures were deployed using a frameless stereotactic technique, both for the collection of biopsy pathological specimens for diagnosis and insertion of drainage in the treatment of intracranial cystic lesions. Results: Twelve patients (eight males, four females) underwent the frameless stereotactic procedure. Mean age at surgery was 55 (±5 SE). The mean volume of the lesion was 23.85 cm 3 (±3.13). Six diagnostic biopsies and six cyst drainages were performed. The mean trajectory length was 75.9 ± 11.8 mm. Three posterior fossa lesions (27%) were approached through a retro-sigmoidal burr-hole. A craniotomy for draining a haematoma was performed after detection with AIRO-CT. No permanent neurological dysfunction, in-hospital or 30-day mortality were recorded. Conclusion: The AIRO-CT resulted feasible with a potential utility for stereotactic procedures. We showed how it could grant the efficacy of the stereotactic procedures reducing some technical and physical sources of inaccuracy, also enhancing safety and allowing prompt detection and management of intraoperative complications.